The influences of safety culture towards safety performance: A case of Convatec, Sungai Petani, Kedah - Hazlyena Annur, Che Hamid (2015)
The primary objective of this study is to study about the dependency of safety culture towards safety performance in Convatec, Sungai Petani which located in Kedah. In this context, the main aim is to determine the influences of safety culture towards safety performance in the workplace. Mixed method is used in this study which is quantitative as a main approach and supported by qualitative approaches. Data for quantitative method were collected from 120 employees included executive and non-executive of Convatec. Findings from this study indicated that a majority of the influences of safety culture is from commitment and support from all level of employees. Result from this study suggested that with limited resources in the company and at the same time reducing the occupational injuries, this company should struggle with how to best focus these resources to achieve the greatest reduction in injuries for the optimal cost. Result also showed that commitment and support has been identified as critical factor that sets the tone for importance of safety culture towards safety performance in Convatec